Genotyping versus phenotyping of non-ABO erythrocyte antigens in patients with the Mediterranean hemopathic syndromes: Effect of transfusion therapy. - Eman NasrEldin (Public Library of Science (PLoS), 2021)
The Mediterranean hemopathic syndromes (MHS) are the most prevalent hemoglobinopathies in the Mediterranean basin. Transfusion therapy is the main therapy for these disorders, particularly for severe forms of the disease. Currently, pre-transfusion serological typing of erythrocyte antigens is the standard tool for reducing complications of transfusion in those patients. This study compared genotyping with phenotyping of non-ABO erythrocyte antigens in patients with MHS and assessed the effect of transfusion therapy on their results. One-hundred ninety-eight MHS patients were recruited, screened, and proven negative for allo-antibodies. They were grouped into two groups: (1) 20 newly diagnosed patients with no transfusion history and (2) 178 previously diagnosed patients undergoing transfusion therapy. Patients were interviewed and clinically examined. Full blood count (FBC) and high performance liquid chromatography (HPLC) were done for group 1 only. Genotyping and phenotyping of non-ABO erythrocyte antigens were performed for group 1, and 25 patients out of group 2 were propensity score-matched (PSM) with group 1. Both groups were gender and age matched; 55% and 74% of groups 1 and 2 had major disease, respectively. Insignificant differences were observed between genotyping and phenotyping of non-ABO erythrocyte antigens in group 1, while significant discrepancies and mixed field results were noted in group 2 patients. Discrepancies were obvious with JKa, JKb, and little c antigens. Conclusively, molecular typing is a powerful tool for pre-transfusion testing in chronically transfused MHS patients. This testing reduces incidence of transfusion reactions. JKa, JKb and little c antigens are the most clinically significant non-ABO erythrocyte antigens.